2006
DOI: 10.1007/s00441-005-0113-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol and dihydrotestosterone on hypergravity-induced MAPK signaling and occludin expression in human umbilical vein endothelial cells

Abstract: Female astronauts have been reported to have a higher incidence of post-flight orthostatic intolerance (POI) compared with that of their male counterparts. POI may result from increased permeability of the endothelial cell (EC) layer in the vasculature. The goal of this study has been to determine whether estradiol (E(2)) and dihydrotesterone (DHT) alter human umbilical vein ECs (HUVECs) responses to short term (10 min) hypergravity (1-3 g) mimicking the g force experienced by astronauts during liftoff. E(2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Very different stimulation modalities have been used (continuous or discontinuous, g forces ranging from 2 to 2,000×g, treatments ranging from minutes to days). This could be the reason for contrasting results sometimes obtained by the authors on ECs (Spisni et al 2003;Versari et al 2007;Sumanasekera et al 2006Sumanasekera et al , 2007. Till now the studies have been conducted in HUVECs, where prolonged hypergravity exposure results in inhibited cell growth, enhanced migration and increased NO synthesis (Spisni et al 2003;Versari et al 2007).…”
Section: Discussionmentioning
confidence: 75%
“…Very different stimulation modalities have been used (continuous or discontinuous, g forces ranging from 2 to 2,000×g, treatments ranging from minutes to days). This could be the reason for contrasting results sometimes obtained by the authors on ECs (Spisni et al 2003;Versari et al 2007;Sumanasekera et al 2006Sumanasekera et al , 2007. Till now the studies have been conducted in HUVECs, where prolonged hypergravity exposure results in inhibited cell growth, enhanced migration and increased NO synthesis (Spisni et al 2003;Versari et al 2007).…”
Section: Discussionmentioning
confidence: 75%
“…The activations of FAK and RhoA were observed shortly after the application of hypergravity, and the latter was declined in 10 min, thereby suggesting that these are the initial signals activated by hypergravity. Previous reports showed the inhibition of MAPK phosphorylation [27] and the activation of cyclooxygenase 2 and prostacyclin synthase [24] after the application of hypergravity for 7.5 min and 24 h, respectively, in HUVECs. The former report also described that the inhibition of MAPK persisted at least for 4 h after returning to 1 G gravity [27], whereas hypergravity-induced FAK phosphorylation declined in 20 min in 1 G (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…They also showed that hypogravity stimulated endothelial growth, enhanced nitric oxide production, and altered actin distribution [29]. Sumanasekera et al reported that brief hypergravity decreased the barrier function, which was attributed to the inhibition of MAPK phosphorylation, in HUVECs [26,27].…”
Section: Introductionmentioning
confidence: 94%
“…There will always be a certain amount of vibrations. In addition, there are before and after each phase of microgravity two phases of hypergravity of 1.8 g. The influence of hypergravity on endothelial cells has been studied before, but with different g-forces (3 g ) and different durations of exposure (10 min and 48 h, respectively) [21,22]. Vibrations, however, have not been intensively investigated.…”
Section: Introductionmentioning
confidence: 99%